Virtual endoscopy and 3D volume rendering in the management of frontal sinus fractures - Belina, Stanko (Array, 2009)
Frontal sinus fractures (FSF) are commonly caused by traffic accidents, assaults, industrial accidents and gunshot wounds. Classical roentgenography has high proportion of false negative findings in cases of FSF and is not particularly useful in examining the severity of damage to the frontal sinus posterior table and the nasofrontal duct region. High resolution computed tomography was inavoidable during the management of such patients but it may produce large quantity of 2D images. Postprocessing of datasets acquired by high resolution computer tomography from patients with severe head trauma may offer a valuable additional help in diagnostics and surgery planning. We performed virtual endoscopy (VE) and 3D volume rendering (3DVR) on high resolution CT data acquired from a 54-year-old man with with both anterior and posterior frontal sinus wall fracture in order to demonstrate advantages and disadvantages of these methods.